AWAKENING WOMEN'S AGENCY THROUGH ORGANIZATIONS: Legal Attitude of Muslim Women Victims of Marital Rape - Sipayung, Ardhina Shafa; Sahid, Mualimin Mochammad (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
This article sheds light on the legal attitude of Muslim women who have been victims of marital rape. The research data came from an examination of twelve court decisions in Indonesia containing cases of marital rape, completed by interviews. After conducting research, it is safe to say that the attitude of Muslim women who choose to divorce their husbands is a form of independence for these women in order to prevent various forms of sexual violence in their lives. Muslim women who take criminal action by reporting their husbands to the police argue that it has a more significant impact on the perpetrators. This latter option is inextricably linked to advocacy from women's agencies, namely the National Commission on Women, the Office of Women's Empowerment and Child Protection (DP3A), and the Integrated Service for Women and Children (P2TPA).[Artikel ini mengulas sikap hukum perempuan muslim korban pemerkosaan dalam perkawinan. Data penelitian ini diambil dari analisis dua belas putusan pengadilan di Indonesia yang berisi kasus marital rape, dilengkapi dengan wawancara. Setelah melakukan penelitian, disimpulkan bahwa para perempuan muslim korban pemerkosaan dalam perkawinan yang memilih jalur perdata dengan menggugat cerai suaminya merupakan bentuk independensi perempuan tersebut untuk menghindari diri dari berbagai bentuk kekerasan seksual. Perempuan muslim korban pemerkosaan dalam perkawinan yang memilih jalur pidana (melaporkan suaminya ke polisi) berdalih memberikan dampak yang lebih signifikan kepada pelaku. Pilihan yang terakhir ini tidak terlepas dari adanya advokasi dari agensi perempuan, yakni: Komnas Perempuan, Dinas Pemberdayaan Perempuan dan Perlindungan Anak (DP3A), dan Pusat Pelayanan Terpadu Perempuan dan Anak (P2TPA).]